A method for preparing underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring.
Patent Information
- Application Number
- CN202610959583.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-27
AI Technical Summary
然而,实践表明HPMC在低温条件下存在显著缺陷:一是低温下HPMC水合速度变慢,溶解性下降,需长时间搅拌或热水预溶,现场施工不便;二是HPMC溶液在低温下粘度激增,导致固化土浆体流动性急剧降低,影响泵送和浇筑;三是HPMC形成的线性网络结构在动水冲刷过程中易被破坏,抗分散效果大幅削弱
[0039](1)本发明采用的低温抗分散一体化助剂由两性离子聚丙烯酰胺、疏水改性凹凸棒土、纳米纤维素和无氯低温水化促凝剂按特定比例复配而成,构建了抗冲刷新机制,配合无氯低温水化促凝剂的快速固化作用,在5℃低温、0.5m/s动水冲刷工况下悬浊物含量低至86mg/L、水泥流失量低至4.4%,显著优于传统HPMC体系。
Smart Images

Figure CN122977804A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of underwater engineering building materials and geotechnical engineering solidification technology, specifically to an underwater non-dispersible fluid solidified soil adapted to low-temperature dynamic water scouring environment and its preparation method. Background Technology
[0002] Underwater non-dispersible materials (NDFs) can be directly cast in flowing water without significant particle dispersion or segregation. They are crucial materials in key areas such as hydraulic engineering, riverbank reinforcement, underwater bridge foundation protection, underwater pipeline coverage and protection, and urban underground engineering. The core technology of underwater NDFs involves incorporating water-soluble polymeric anti-dispersants into ordinary concrete mixtures. Through the "bridging" and adsorption effects of the long polymer chains, the viscosity of the cement paste is significantly increased, allowing cement particles and aggregates to effectively resist erosion and dilution during casting in water. This reduces cement loss and ensures the strength and durability of the final structure.
[0003] In recent years, fluidized solidified soil has gradually become an important technical approach for underwater backfilling and protection projects due to its good fluidity, self-compacting properties, and the ability to utilize engineering waste soil. However, in water conservancy projects in low-temperature winter environments or high-altitude and cold regions, underwater construction faces low-temperature environments below 5°C or even close to 0°C, often accompanied by strong dynamic water scouring (flow velocity 0.3–1.0 m / s). The coupled effect of low temperature and dynamic water scouring places extremely stringent performance requirements on underwater non-dispersible fluidized solidified soil.
[0004] Currently, hydroxypropyl methylcellulose (HPMC) is commonly used as the core component of underwater non-dispersible materials. HPMC increases the viscosity of the slurry through thickening and physical entanglement, thereby limiting the dispersion of cement and soil particles. However, practice has shown that HPMC has significant drawbacks at low temperatures: First, the hydration rate of HPMC slows down and its solubility decreases at low temperatures, requiring prolonged stirring or pre-dissolving in hot water, which is inconvenient for on-site construction; second, the viscosity of HPMC solution surges at low temperatures, leading to a sharp decrease in the fluidity of the solidified soil slurry, affecting pumping and pouring; third, the linear network structure formed by HPMC is easily destroyed during the scouring process of flowing water, significantly weakening the anti-dispersibility effect. At the same time, the early-strength components in existing technologies (such as calcium formate and lithium silicate) have limited promoting effects at low temperatures, making it difficult for the material to form sufficient scouring strength within 2-4 hours after pouring.
[0005] There is a small amount of underwater solidification technology for construction waste soil, but it has not been specifically modified to address the characteristics of construction waste soil particles being mixed, having high porosity, being hydrophilic, and having high water absorption. The soil particles are prone to water absorption and disintegration in low-temperature water environments, resulting in problems such as aggregate segregation and slurry stratification loss. Existing underwater non-dispersible fluid materials are mostly based on pure cement and natural sand and gravel, which are only suitable for construction and service in normal temperature still water environments. They have three major technical shortcomings: (1) Base material limitations: Traditional hydraulic materials rely on natural sand and gravel aggregates, resulting in low solid waste disposal rates and high engineering costs. The existing small amount of underwater solidification materials based on construction waste have not been targeted for modification to address the inherent characteristics of mixed waste bricks and mortar blocks, high porosity, hydrophilic surface, and high water absorption. In low-temperature water environments, they are prone to problems such as particle water absorption and disintegration, aggregate segregation, and slurry stratification and loss. (2) Poor adaptability to working conditions: Most underwater non-dispersible materials on the market are only suitable for room temperature still water conditions. In the harsh working conditions of low temperature (0-5℃) and dynamic water flow scouring, the hydration reaction of ordinary cement is almost stagnant, and the low-temperature activity of conventional HPMC+anionic PAM anti-dispersibility system is greatly reduced and it fails quickly. (3) Defects in the additive system: Traditional anti-dispersibility additives have no low-temperature adaptability design. In low-temperature environments, the activity of polymeric additive molecular chains is reduced, the encapsulation and locking ability fails, and a continuous and stable particle encapsulation network cannot be formed. Furthermore, they cannot resist the micro-scouring shear stress generated by the continuous surging of low-temperature dynamic water.
[0006] Therefore, there is an urgent need to develop an underwater non-dispersible fluidized solidified soil that can replace HPMC, has excellent erosion resistance in low-temperature hydrodynamic coupling environment, and is green and low-carbon, as well as its preparation method. Summary of the Invention
[0007] To address the aforementioned problems in the prior art, this invention provides an underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring and its preparation method.
[0008] The technical solution of this invention is as follows:
[0009] A non-dispersible fluidized solidified soil suitable for low-temperature dynamic water scouring is characterized in that the raw materials include the following components in the following mass proportions: 70-85 parts of pretreated construction waste, 12-25 parts of low-temperature composite cementitious system, and 1.5-3.0 parts of low-temperature anti-dispersion integrated additive.
[0010] The low-temperature composite cementitious system is composed of rapid-hardening sulfoaluminate cement, slag powder, and calcium carbide slag powder in a mass ratio of 4-8:5-10:3-8.
[0011] The low-temperature anti-dispersion integrated additive is composed of amphoteric polyacrylamide, hydrophobically modified attapulgite, nanocellulose, and chlorine-free low-temperature hydration accelerator in a mass ratio of 0.04-0.12:1.0-2.2:0.1-0.35:0.3-0.5.
[0012] Those skilled in the art will understand that the pretreated construction waste refers to construction waste (mainly including waste concrete blocks, bricks, tiles, mortar blocks, etc.) that has undergone crushing, screening, impurity removal, and drying. After pretreatment, the surface hydrophilicity and porosity of the waste particles are improved to a certain extent, providing a stable aggregate substrate for the low-temperature anti-dispersion integrated additive of the present invention. Those skilled in the art can directly pretreat the construction waste according to the above method, or directly purchase construction waste that meets the particle size and moisture content requirements.
[0013] Those skilled in the art will understand that the aforementioned 42.5 grade rapid-hardening sulfoaluminate cement refers to rapid-hardening sulfoaluminate cement that conforms to the corresponding standard in the national standard GB / T20472-2006. This type of cement uses anhydrous calcium sulfoaluminate and dicalcium silicate as its main mineral components, exhibits a rapid hydration reaction rate at low temperatures, and can provide early strength at 5°C. Skilled personnel can directly purchase commercially available products that meet the above specifications from the market.
[0014] Those skilled in the art will understand that the S95 grade slag powder refers to S95 grade slag powder that conforms to the national standard "Granulated Blast Furnace Slag Powder for Cement, Mortar and Concrete" (GB / T 18046). In this invention, the slag powder undergoes a secondary hydration reaction with cement hydration products, improving later-stage strength and density; on the other hand, it works synergistically with calcium carbide slag powder, utilizing the alkalinity of the calcium carbide slag powder to activate its pozzolanic activity. Those skilled in the art can purchase this directly from the market.
[0015] Those skilled in the art will understand that the calcium carbide slag powder is an industrial waste residue generated during the hydrolysis of calcium carbide to produce acetylene, which is obtained after drying and grinding. In this invention, the calcium carbide slag powder serves as an alkaline activator, increasing the pH value of the slurry and activating the pozzolanic activity of the slag powder. It also partially replaces cement, reducing costs and carbon emissions. Those skilled in the art can prepare it themselves or purchase commercially available products meeting the fineness and purity requirements from calcium carbide slag recycling enterprises.
[0016] In this invention, the zwitterionic polyacrylamide is a zwitterionic polymer copolymerized from acrylamide and monomers containing both cationic and anionic groups, with its molecular chains carrying both positive and negative charges. This material maintains a stable configuration in alkaline cement paste (pH≈12) and rapidly flocculates negatively charged slag and cement particles through charge neutralization and adsorption bridging. Technical personnel can purchase zwitterionic polyacrylamide of appropriate specifications directly from the market, such as from Beijing Hengju Chemical Group, or prepare it themselves using known solution polymerization methods.
[0017] In this invention, the hydrophobically modified attapulgite is a product obtained by surface hydrophobic modification of natural attapulgite using a silane coupling agent. While unmodified natural attapulgite possesses a large specific surface area and adsorption capacity, its surface is rich in hydrophilic silanol groups, resulting in insufficient resistance to water wetting under flowing water. This invention uses a silane coupling agent (such as hexadecyltrimethoxysilane, octyltriethoxysilane, etc.) to hydrophobically modify it, forming a hydrophobic layer on the particle surface, thereby significantly enhancing its resistance to erosion in flowing water. Technical personnel can prepare it themselves using conventional wet or dry modification processes, or commission a professional manufacturer to produce it, or purchase it from the market.
[0018] In this invention, the nanocellulose is cellulose nanofiber or cellulose nanocrystal. Nanocellulose has an extremely high aspect ratio and abundant surface hydroxyl groups, enabling it to form a three-dimensional nanonetwork in a slurry through hydrogen bonding and physical entanglement. Technicians can purchase CNF or CNC products directly from the market, such as those produced by CelluForce (USA) or Tianjin Wood Elf Biotechnology Co., Ltd., or prepare them themselves using a TEMPO oxidation combined with high-pressure homogenization method.
[0019] In this invention, the chlorine-free low-temperature hydration accelerator is a complex composed of triethanolamine and aluminum sulfate, or a complex composed of calcium formate and lithium carbonate. This accelerator can accelerate the hydration process of sulfoaluminate cement at a low temperature of 5°C, promoting the rapid formation of hydration products such as ettringite. Technicians can directly mix and grind triethanolamine and aluminum sulfate (or calcium formate and lithium carbonate) in a specific ratio, or customize or purchase ready-made products from admixture manufacturers.
[0020] In the above technical solution, pretreated construction waste serves as the main aggregate and filling material for fluidized solidified soil, realizing the resource utilization of construction solid waste. In the low-temperature composite cementitious system, rapid-hardening sulfoaluminate cement provides rapid hydration and early strength under low-temperature conditions; slag powder provides pozzolanic activity, undergoing a secondary hydration reaction with cement hydration products to improve later-stage strength and compactness; calcium carbide slag powder provides an alkaline activation environment, activating the pozzolanic activity of the slag powder and improving hydration kinetics at low temperatures. The components synergistically form a low-temperature rapid-hardening, long-term strength, and cost-controlled cementitious system.
[0021] As a further improvement of the present invention, the pretreated construction waste has a particle size ≤4.75mm and a moisture content ≤10%; the rapid-hardening sulfoaluminate cement is grade 42.5 rapid-hardening sulfoaluminate cement with a specific surface area ≥350m² / kg and an initial setting time ≤25min; the slag powder is grade S95 slag powder with a specific surface area ≥400m² / kg and a 28d activity index ≥95%; the calcium carbide slag powder is dried, ground, and passed through a 200-mesh sieve, with a Ca(OH)₂ content ≥85%.
[0022] This constraint ensures that the particle size of construction waste matches the uniformity and flowability requirements of the solidified soil slurry. If the particle size of the construction waste is too large, it will be difficult to disperse evenly in the slurry, easily leading to aggregate segregation; if the moisture content is too high, it will affect the final consolidation performance of the solidified soil slurry. At the same time, cementitious materials that meet the above indicators can ensure that the low-temperature composite cementitious system maintains a high hydration reaction rate and strength development level below 5°C.
[0023] As a further improvement of the present invention, the zwitterionic polyacrylamide is a copolymer of acrylamide, whose molecular chain contains both cationic and anionic groups, with a molecular weight of 8 million to 12 million, a cationicity of 10% to 30%, an anionicity of 5% to 15%, and a solid content ≥90%. The above parameter range represents the optimal process parameter range obtained by the inventors through extensive experimental screening. Molecular weight and cationicity affect its adsorption and flocculation effect; a suitable molecular weight range ensures both effective flocculation and prevents excessively high slurry viscosity.
[0024] As a further improvement of the present invention, the hydrophobically modified attapulgite is prepared by surface hydrophobic modification of natural attapulgite using a silane coupling agent, with a hydrophobic contact angle ≥120° and a specific surface area ≥150m² / g. The hydrophobic contact angle of the hydrophobically modified attapulgite determines the strength of its hydrophobic shielding effect, and the high specific surface area provides sufficient physical adsorption sites; both work synergistically to enhance the anti-dispersion effect.
[0025] As a further improvement of the present invention, the nanocellulose is cellulose nanofiber or cellulose nanocrystal, with a diameter of 5-20 nm, a length of 200-2000 nm, and a crystallinity ≥70%. The size and crystallinity of nanocellulose affect its dispersibility in slurry and the construction effect of three-dimensional network. Nanoscale and high aspect ratio are key to forming a stable nanonetwork.
[0026] As a further improvement of the present invention, the chloride-free low-temperature hydration accelerator is a composite composed of triethanolamine and aluminum sulfate in a mass ratio of 1:2 to 3, or a composite composed of calcium formate and lithium carbonate in a mass ratio of 5 to 10:1. Both of these composites are chloride-free, avoiding the risk of steel reinforcement corrosion, and can effectively promote the hydration reaction of sulfoaluminate cement at low temperatures.
[0027] The underwater non-dispersible fluidized solidified soil adapted for low-temperature dynamic water scouring of the present invention can be prepared by the following method:
[0028] S1. Take each raw material according to the production raw material quantity;
[0029] S2. Add rapid-hardening sulfoaluminate cement, slag powder, and carbide slag powder into a dry powder mixer and stir at a low speed of 140-200 r / min for 5-10 min to ensure that the dry powder components are evenly dispersed and to obtain a premixed dry material.
[0030] S3. Mix hydrophobically modified attapulgite and nanocellulose, add to mixing water, and stir in a high-speed disperser at 1000-2000 r / min for 10-15 min to fully disperse and form a stable suspension; then add zwitterionic polyacrylamide and chlorine-free low-temperature hydration accelerator, and continue stirring for 5-10 min to obtain the anti-dispersion aid pre-dispersion liquid.
[0031] S4. The premixed dry material obtained in step S2 is put into a forced mixer. First, the anti-dispersion agent pre-dispersion liquid obtained in step S3 and the mixing water are added. The mixture is stirred at a low speed of 120-180 r / min for 2-4 min to form a solidifying agent slurry. Then, the pretreated construction waste is slowly added and stirred at a low speed for 5-10 min to ensure that all components are fully mixed and homogeneous, so as to obtain a fluid solidified soil slurry with a solid content of 65%-75%.
[0032] S5. The fluidized solidified soil slurry prepared in step S4 is injected into the mold and cured to the specified age to obtain fluidized solidified soil.
[0033] In step S2, the components of the cementitious material are premixed as dry powder, which facilitates the full and uniform dispersion of each component during the subsequent wet mixing process. In step S3, the hydrophobically modified attapulgite and nanocellulose are pre-dispersed in water under high-speed dispersion conditions to ensure that the two components form a uniform and stable suspension system. Then, zwitterionic polyacrylamide and chlorine-free low-temperature hydration accelerator are added to avoid agglomeration problems caused by premature contact of polymer molecules. In step S4, the order of mixing the curing agent slurry first and then adding the construction waste ensures that the cementitious material first forms a uniform and stable slurry network, and then the construction waste particles are uniformly coated and dispersed through this network to achieve the optimal particle coating effect. By controlling the amount of mixing water, the solid content of the resulting fluidized solidified soil slurry is 65% to 75%, which balances good fluidity, self-compacting, and anti-dispersion properties.
[0034] As a further improvement of the present invention, when the construction water temperature is below 5°C, the mixing water in steps S3 and S4 is preheated to 18-22°C. Under extreme conditions where the construction water temperature is below 5°C, moderate preheating of the mixing water can effectively improve the dispersion effect of hydrophobic modified attapulgite and nanocellulose, while reducing the inhibition of cement hydration by low temperature.
[0035] It should be noted that the fluidized solidified soil slurry prepared in step S4 should preferably be poured underwater within 30 minutes to ensure that the material is used during the window of optimal fluidity and anti-dispersion performance.
[0036] The present invention also discloses the application of the underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring in water conservancy projects, river embankment reinforcement, underwater bridge foundation protection, or underwater pipeline covering protection.
[0037] Beneficial effects:
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The low-temperature anti-dispersion integrated additive used in this invention is composed of zwitterionic polyacrylamide, hydrophobic modified attapulgite, nanocellulose and chlorine-free low-temperature hydration accelerator in a specific ratio, which constructs an anti-erosion and refreshing mechanism. Combined with the rapid curing effect of the chlorine-free low-temperature hydration accelerator, the suspended solids content is as low as 86mg / L and the cement loss is as low as 4.4% under the working conditions of 5℃ low temperature and 0.5m / s dynamic water flushing, which is significantly better than the traditional HPMC system.
[0040] (2) The experiment shows that the fluidized solidified soil prepared by the method of the present invention has a fast early strength development at low temperature (5℃), and the compressive strength of 4h reaches more than 0.30MPa. The strength ratio of dynamic water and static water under 28d conditions is maintained at more than 95%, which makes the fluidized solidified soil and its preparation method break through the seasonal and regional temperature limitations, and the construction window period is significantly extended.
[0041] (3) The method of the present invention can dispose of a large amount of industrial solid waste such as construction waste, slag powder and calcium carbide slag powder, significantly reduce cement consumption and carbon emissions, and has excellent environmental and economic benefits. Attached Figure Description
[0042] Figure 1 This is a process flow diagram of Embodiment 1 of the specific implementation method. Detailed Implementation
[0043] To enable those skilled in the art to better implement the present invention, the present invention will be further described below with reference to embodiments. However, it should be understood that the present invention is not limited to the following embodiments.
[0044] For ease of comparison, the raw materials used in the following examples and comparative examples are all from the same batch, and the specific parameters of the raw materials are as follows:
[0045] Pretreated construction waste: particle size ≤ 4.75mm, moisture content 2.8%, mud content 2.1%, organic matter content 0.5%, density 2.66g / cm³.
[0046] Grade 42.5 rapid-hardening sulfoaluminate cement: specific surface area 362m² / kg, initial setting time 22min, final setting time 165min, 3d compressive strength 45.2MPa, 28d compressive strength 54.8MPa.
[0047] S95 grade slag powder: specific surface area 418m² / kg, density 2.91g / cm³, fluidity ratio 97%, 7d activity index 78%, 28d activity index 97%, moisture content 0.6%.
[0048] Calcium carbide slag powder (200 mesh): Ca(OH)2 content 88.5%, fineness (200 mesh sieve residue) 3.2%, moisture content 1.1%, MgO content 1.5%, SiO2 content 2.3%.
[0049] Amphoteric polyacrylamide: molecular weight 9.8 million, cationicity 22%, anionicity 9%, solid content 92%, degree of hydrolysis 8%, residual monomer content 0.02%.
[0050] Hydrophobic modified attapulgite: hydrophobic contact angle 128°, specific surface area 168m² / g, modifier dosage 3% of attapulgite mass, particle size (D90) 8.5μm, loss on drying 3.2%, pH value (10% suspension) 7.8.
[0051] Cellulose nanofibers (CNF) with a diameter of 12 nm, a length of 850 nm, a crystallinity of 75%, a carboxyl content of 1.2 mmol / g, a solid content of 2.5% (in gel form), and an ash content of 0.6%.
[0052] Chlorine-free low-temperature hydration coagulant: a composite of triethanolamine and aluminum sulfate in a mass ratio of 1:2.5; fineness (200 mesh sieve residue) 1.5%, purity 96.5%.
[0053] Example 1
[0054] The following method was used to prepare fluidized solidified soil:
[0055] S1. Measure the raw materials according to the following production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, and 2.3 parts low-temperature anti-dispersion integrated additive; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder; the low-temperature anti-dispersion integrated additive consists of 0.07 parts zwitterionic polyacrylamide, 1.6 parts hydrophobically modified attapulgite, 0.22 parts nanocellulose, and 0.45 parts chlorine-free low-temperature hydration accelerator. Simultaneously measure the mixing water to ensure the final slurry solids content reaches 68%.
[0056] S2. The 42.5 grade rapid hardening sulfoaluminate cement, S95 grade slag powder, and carbide slag powder are put into a dry powder mixer and stirred at a stirring speed of 140 r / min for 5 min to make the dry powder components evenly dispersed and to obtain a premixed dry material.
[0057] S3. Mix the hydrophobic modified attapulgite and nanocellulose, add them to the mixing water, and stir in a high-speed disperser at a stirring speed of 1500 r / min for 12 min to fully disperse them and form a stable suspension; then add zwitterionic polyacrylamide and chlorine-free low-temperature hydration accelerator, and continue stirring for 8 min to obtain the anti-dispersion aid pre-dispersion liquid.
[0058] S4. The premixed dry material obtained in step S2 is put into a forced mixer. First, the anti-dispersion agent pre-dispersion liquid obtained in step S3 and the remaining mixing water are added. The mixture is stirred at a stirring rate of 140 r / min for 3 min to form a solidifying agent slurry. Then, the pretreated construction waste is slowly added and stirred for 8 min to ensure that all components are fully mixed and homogeneous, so as to obtain a fluid solidified soil slurry with a solid content of 68%.
[0059] S5. The fluidized solidified soil slurry was injected into a mold with dimensions of 70.7×70.7×70.7mm and cured in still water at 20℃ for 7 days and 28 days. Samples were taken and the properties of the fluidized solidified soil were tested. The results are shown in Table 1.
[0060] Example 2
[0061] The procedure is the same as in Example 1, except that the curing temperature is adjusted (5°C static water). The specific plan is as follows:
[0062] S1 to S4 are the same as in Example 1, and a fluidized solidified soil slurry with a solid content of 68% is obtained.
[0063] S5. The fluidized solidified soil slurry was injected into a mold with dimensions of 70.7×70.7×70.7mm and cured in still water at 5℃ for 7 days and 28 days. Samples were taken and the properties of the fluidized solidified soil were tested. The results are shown in Table 1.
[0064] Example 3
[0065] The procedure is the same as in Example 1, except that the curing conditions (5°C flowing water) are adjusted. The specific plan is as follows:
[0066] S1 to S4 are the same as in Example 1, and a fluidized solidified soil slurry with a solid content of 68% is obtained.
[0067] S5. The fluidized solidified soil slurry was injected into a 70.7×70.7×70.7mm mold and placed in 5℃ flowing water (flow rate 0.5m / s) for curing. After curing for 7d and 28d, samples were taken to test the properties of the fluidized solidified soil. The results are shown in Table 1.
[0068] Example 4
[0069] The procedure is the same as in Example 1, except that the dosage of the integrated low-temperature anti-dispersion agent is adjusted and the mixture is cured in still water at 5°C. The specific procedure is as follows:
[0070] S1. Measure the raw materials according to the following production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, and 2.7 parts low-temperature anti-dispersion integrated additive; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder; the low-temperature anti-dispersion integrated additive consists of 0.09 parts zwitterionic polyacrylamide, 1.9 parts hydrophobically modified attapulgite, 0.25 parts nanocellulose, and 0.47 parts chlorine-free low-temperature hydration accelerator. Simultaneously measure the mixing water to ensure the final slurry solids content reaches 68%.
[0071] S2 to S5 were prepared in the same way as in Example 1. The fluidized solidified soil was cured in still water at 5°C. The results are shown in Table 1.
[0072] Example 5
[0073] The procedure is the same as in Example 1, except that the dosage of the integrated low-temperature anti-dispersion agent is adjusted and the mixture is cured in still water at 5°C. The specific procedure is as follows:
[0074] S1. Measure the raw materials according to the following production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, and 1.9 parts low-temperature anti-dispersion integrated additive; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder; the low-temperature anti-dispersion integrated additive consists of 0.05 parts zwitterionic polyacrylamide, 1.3 parts hydrophobically modified attapulgite, 0.18 parts nanocellulose, and 0.37 parts chlorine-free low-temperature hydration accelerator. Simultaneously measure the mixing water to ensure the final slurry solids content reaches 68%.
[0075] S2 to S5 were prepared in the same way as in Example 1. The fluidized solidified soil was cured in still water at 5°C. The results are shown in Table 1.
[0076] Comparative Example 1
[0077] This comparative example serves as a control experiment for Example 1, and is conducted according to the same steps as Example 1, except that no anti-dispersing agent is added; that is, step S1 does not contain the integrated low-temperature anti-dispersing agent component and is maintained in still water at 5°C. The specific scheme is as follows:
[0078] S1. Measure the raw materials according to the following production raw material formula: 76 parts of pretreated construction waste soil, and 18 parts of low-temperature composite cementitious system; the low-temperature composite cementitious system consists of 6 parts of 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts of S95 grade slag powder, and 5 parts of calcium carbide slag powder. Simultaneously measure the mixing water to ensure the final slurry solid content reaches 68%.
[0079] S2. Place the 42.5 grade rapid hardening sulfoaluminate cement, S95 grade slag powder, and carbide slag powder in a mixer and stir at a stirring speed of 140 r / min for 5 min to uniformly disperse the dry powder components and obtain the premixed dry material.
[0080] S3. Add mixing water to the premixed dry material and stir at a stirring rate of 140 r / min for 3 min to obtain a curing agent slurry. Then slowly add the pretreated construction waste soil and stir for 8 min to ensure that all components are fully mixed and homogeneous, thereby obtaining a fluidized solidified soil slurry with a solid content of 68%.
[0081] S4. The fluidized solidified soil slurry was injected into a 70.7×70.7×70.7mm mold and cured in still water at 5℃ for 7 days and 28 days. The results of the fluidized solidified soil were then tested and the properties were shown in Table 1.
[0082] Comparative Example 2
[0083] This comparative example serves as a control experiment for Example 1, conducted according to the same steps as Example 1, except that: a traditional HPMC anti-dispersion system is used instead of the low-temperature integrated anti-dispersion agent of this invention, and it is cured in dynamic water at 5°C. The specific scheme is as follows:
[0084] S1. Measure the following raw materials according to the production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, 1.8 parts HPMC (150000mPa·s), 0.5 parts nonionic PAM, 2 parts calcium formate, and 0.4 parts water-reducing agent; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder. Simultaneously measure the mixing water to ensure the final slurry solid content reaches 68%.
[0085] S2. Place the 42.5 grade rapid hardening sulfoaluminate cement, S95 grade slag powder, and carbide slag powder in a mixer and stir at a stirring speed of 140 r / min for 5 min to uniformly disperse the dry powder components and obtain the premixed dry material.
[0086] S3. Add the HPMC (150000mPa·s), nonionic PAM, calcium formate, and water-reducing agent to the mixing water, and stir in a high-speed disperser at a stirring speed of 1500r / min for 12min to fully disperse them and form an anti-dispersing agent dispersion.
[0087] S4. First, add the anti-dispersing agent dispersion obtained in step S3 and the remaining mixing water to the premixed dry material, and stir at a stirring rate of 140 r / min for 3 min to obtain the curing agent slurry. Then, slowly add the pretreated construction waste soil and stir for 8 min to ensure that all components are fully mixed and homogeneous, so as to obtain a fluidized solidified soil slurry with a solid content of 68%.
[0088] S5. The fluidized solidified soil slurry was injected into a 70.7×70.7×70.7mm mold and placed in 5℃ flowing water (flow rate 0.5m / s) for curing. After curing for 7d and 28d, samples were taken to test the properties of the fluidized solidified soil. The results are shown in Table 1.
[0089] Comparative Example 3
[0090] This comparative example serves as a control experiment for Example 3, conducted according to the same procedures as Example 3, except that hydrophobic modified attapulgite is not added to the low-temperature anti-dispersion integrated additive (total amount the same as in Example 3). The specific scheme is as follows:
[0091] S1. Measure the raw materials according to the following production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, and 2.3 parts low-temperature anti-dispersion integrated additive; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder; the low-temperature anti-dispersion integrated additive consists of 0.22 parts zwitterionic polyacrylamide, 0.68 parts nanocellulose, and 1.40 parts chlorine-free low-temperature hydration accelerator (the three are scaled up proportionally to a total of 2.3 parts). Simultaneously measure the mixing water to ensure the final slurry solids content reaches 68%.
[0092] S2 to S4 are the same as in Example 3.
[0093] S5. The fluidized solidified soil slurry was injected into a 70.7×70.7×70.7mm mold and placed in 5℃ flowing water (flow rate 0.5m / s) for curing. After curing for 7d and 28d, samples were taken to test the properties of the fluidized solidified soil. The results are shown in Table 1.
[0094] Comparative Example 4
[0095] This comparative example serves as a control experiment for Example 3, and is conducted according to the same procedures as Example 3, except that zwitterionic polyacrylamide is not added to the low-temperature anti-dispersion integrated additive (total amount the same as in Example 3). The specific scheme is as follows:
[0096] S1. Measure the raw materials according to the following production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, and 2.3 parts low-temperature anti-dispersion integrated additive; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder; the low-temperature anti-dispersion integrated additive consists of 1.62 parts hydrophobic modified attapulgite, 0.22 parts nanocellulose, and 0.46 parts chlorine-free low-temperature hydration accelerator (the three are scaled up proportionally to a total of 2.3 parts). Simultaneously measure the mixing water to ensure the final slurry solids content reaches 68%.
[0097] S2 to S4 are the same as in Example 3.
[0098] S5. The fluidized solidified soil slurry was injected into a 70.7×70.7×70.7mm mold and placed in 5℃ flowing water (flow rate 0.5m / s) for curing. After curing for 7d and 28d, samples were taken to test the properties of the fluidized solidified soil. The results are shown in Table 1.
[0099] Comparative Example 5
[0100] This comparative example serves as a control experiment for Example 3, and is conducted according to the same steps as Example 3, except that nanocellulose is not added to the low-temperature anti-dispersion integrated additive (total amount the same as in Example 3). The specific scheme is as follows:
[0101] S1. Measure the raw materials according to the following production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, and 2.3 parts low-temperature anti-dispersion integrated additive; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder; the low-temperature anti-dispersion integrated additive consists of 0.08 parts zwitterionic polyacrylamide, 1.74 parts hydrophobic modified attapulgite, and 0.48 parts chlorine-free low-temperature hydration accelerator (the three are scaled up proportionally to a total of 2.3 parts). Simultaneously measure the mixing water to ensure the final slurry solids content reaches 68%.
[0102] S2 to S4 are the same as in Example 3.
[0103] S5. The fluidized solidified soil slurry was injected into a 70.7×70.7×70.7mm mold and placed in 5℃ flowing water (flow rate 0.5m / s) for curing. After curing for 7d and 28d, samples were taken to test the properties of the fluidized solidified soil. The results are shown in Table 1.
[0104] Comparative Example 6
[0105] This comparative example serves as a control experiment for Example 3, and is conducted according to the same steps as Example 3, except that no chlorine-free low-temperature hydration accelerator is added to the low-temperature anti-dispersion integrated additive (total amount the same as in Example 3). The specific scheme is as follows:
[0106] S1. Measure the raw materials according to the following production raw material formula: 76 parts pretreated construction waste, 18 parts low-temperature composite cementitious system, and 2.3 parts low-temperature anti-dispersion integrated additive; the low-temperature composite cementitious system consists of 6 parts 42.5 grade rapid-hardening sulfoaluminate cement, 7 parts S95 grade slag powder, and 5 parts calcium carbide slag powder; the low-temperature anti-dispersion integrated additive consists of 0.09 parts zwitterionic polyacrylamide, 1.95 parts hydrophobic modified attapulgite, and 0.26 parts nanocellulose (the three are scaled up proportionally to a total of 2.3 parts). Simultaneously measure the mixing water to ensure the final slurry solid content reaches 68%.
[0107] S2 to S4 are the same as in Example 3.
[0108] S5. The fluidized solidified soil slurry was injected into a 70.7×70.7×70.7mm mold and placed in 5℃ flowing water (flow rate 0.5m / s) for curing. After curing for 7d and 28d, samples were taken to test the properties of the fluidized solidified soil. The results are shown in Table 1.
[0109] Comparative test of the properties of fluidized solidified soil:
[0110] The fluidized solidified soils prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested according to the following methods:
[0111] (1) Spreadability and compressive strength: The tests were conducted in accordance with the Sichuan Provincial Engineering Construction Local Standard DBJ51 / T 188-2022 "Technical Standard for Engineering Application of Premixed Flowable Solidified Soil". For the spreadability test, a cylindrical test tube with an inner diameter of 75mm and a height of 150mm was used. The mixture was placed into the test tube in two layers, compacted, and leveled. The test tube was then lifted vertically. After the mixture stopped flowing, the maximum diameter in two vertical directions was measured, and the average value was taken as the spreadability value. This index is used to evaluate the construction flowability of the flowable solidified soil slurry. For the cubic compressive strength test, a 70.7mm×70.7mm×70.7mm cubic specimen was used. The specimen was cured to the specified age using standard methods, and a constant loading rate was applied until the specimen failed. The failure load was recorded, and the compressive strength value was calculated. Specimens for the low-temperature test (5℃) were cured in water at the corresponding temperature, maintaining the same temperature as the construction environment.
[0112] (2) Suspended solids content and cement loss: The test was conducted in accordance with the provisions of the power industry standard DL / T 5117-2021 "Test Procedure for Underwater Non-Dispersible Concrete" regarding the test of anti-dispersibility performance. The anti-dispersibility performance of the fluidized solidified soil under water was comprehensively evaluated by two indicators: cement loss and suspended solids content. The free fall in water was controlled to be 500 mm during the test. The specific operation was as follows: 1.5L to 2.0L of fluidized solidified soil slurry was put into an inverted slump cone. The cone was slowly lifted within 60s, allowing the slurry to fall freely in 500mm of water. After standing for 2 minutes, a water sample was taken from 100 to 300mm below the water surface to determine the suspended solids content. After drying the sediment, the cement loss was calculated. During the low-temperature test (5℃ flowing water), in accordance with the provisions of DL / T 5117-2021 that "when the water temperature is <10℃, the on-site water temperature should be used for curing", the pouring and curing were carried out in a flowing water tank (flow velocity 0.5m / s), and the water temperature was kept consistent with the construction environment temperature.
[0113] The experimental results are shown in Table 1.
[0114] Table 1 Analysis of Test Results for Flowable Solidified Soil
[0115] Example 1 20℃ still water 250 36 1.8 0.50 0.78 2.06 Example 2 5℃ still water 242 43 2.2 0.32 0.59 1.62 Example 3 5℃ moving water 242 86 4.4 0.31 0.55 1.55 Example 4 5℃ still water 235 34 1.6 0.39 0.68 1.84 Example 5 5℃ still water 258 60 3.8 0.26 0.47 1.36 Comparative Example 1 (without any dispersant) 5℃ still water 288 185 12.5 — 0.12 0.85 Comparative Example 2 (Traditional HPMC) 5℃ moving water 192 218 16.2 — 0.18 0.72 Comparative Example 3 (lacking H-ATP) 5℃ moving water 257 151 11.0 0.17 0.34 0.96 Comparative Example 4 (Missing AmPAM) 5℃ moving water 254 166 12.3 0.14 0.30 0.89 Comparative Example 5 (Missing CNF) 5℃ moving water 251 130 8.9 0.21 0.41 1.09 Comparative Example 6 (Missing LPA) 5℃ moving water 241 93 5.0 0.07 0.19 0.91
[0116] Note: DL / T 5117-2021 stipulates that the suspended solids content of underwater non-dispersible concrete is ≤150mg / L for superior grade and ≤200mg / L for qualified grade; the cement loss is ≤10% for superior grade and ≤15% for qualified grade. This invention only refers to its test methods and does not directly apply its limits; "—" in the table indicates that the strength cannot be formed.
[0117] Results analysis:
[0118] 1. Overall effectiveness of the low-temperature anti-dispersion integrated additive: As can be seen from the test results of Examples 2 and 3 and Comparative Examples 1 and 2 in Table 1, the fluidized solidified soil prepared using the complete formula of this invention (Examples 2 and 3) has a suspended solids content of 43 mg / L and a cement loss of 2.2% under static water conditions at 5℃, and a suspended solids content of 86 mg / L and a cement loss of 4.4% under dynamic water conditions at 5℃. These are significantly lower than those of Comparative Example 1 (185 mg / L, 12.5%) without any additives and Comparative Example 2 (218 mg / L, 16.2%) with the traditional HPMC formula. This indicates that the low-temperature anti-dispersion integrated additive of this invention can enable the fluidized solidified soil to maintain extremely low dispersion loss under both low-temperature static water and dynamic water conditions, and its anti-dispersion performance is significantly better than that of traditional technical systems.
[0119] 2. Comprehensive Performance under Low-Temperature Dynamic Water Environment: A comparison of Example 3 and Example 2 shows that Example 3, cured under dynamic water conditions at 5℃, exhibits a 28-day compressive strength (1.55 MPa) that is essentially the same as Example 2 (1.62 MPa under static water conditions at 5℃), with a dynamic / static strength ratio of 95.7%. Its 1-day strength (0.55 MPa) is also close to the 0.59 MPa under static water conditions. Crucially, the 4-hour strength (0.31 MPa) of Example 3 is almost identical to the 4-hour strength (0.32 MPa) under static water conditions, indicating that even when cast under dynamic water conditions, the material can still hydrate normally and form sufficient structural strength within 4 hours. Meanwhile, a comparison between Example 2 and Example 1 shows that although the 4-hour strength (0.32 MPa) of Example 2 under low-temperature conditions at 5℃ is lower than the 0.50 MPa at room temperature, it still meets the structural strength required to resist water erosion within 4 hours after casting under low-temperature dynamic water conditions.
[0120] 3. Comparison of Example 3 with Comparative Examples 3, 4, 5, and 6 shows that, under the premise of 5°C dynamic water conditions and the same total amount of low-temperature anti-dispersion integrated additive, when hydrophobically modified attapulgite (Comparative Example 3), amphoteric polyacrylamide (Comparative Example 4), or nanocellulose (Comparative Example 5) are individually lacking, the suspended solids content increases to 151 mg / L, 166 mg / L, and 130 mg / L, respectively; the cement loss increases to 11.0%, 12.3%, and 8.9%, respectively; and the 4-hour strength decreases to 0, respectively. The strengths of 0.17 MPa, 0.14 MPa, and 0.21 MPa were all significantly worse than those of Example 3, which had a complete four-component compound (suspended solids 86 mg / L, loss 4.4%, 4-hour strength 0.31 MPa). When the chlorine-free low-temperature hydration accelerator (Comparative Example 6) was missing alone, although the suspended solids and cement loss remained at a relatively good level (93 mg / L, 5.0%), the 4-hour strength was only 0.07 MPa, a decrease of about 77% compared to Example 3, which completely failed to meet the requirements for low-temperature dynamic water construction. The three comparative examples lacking a single anti-dispersion component all showed significant deterioration in anti-dispersion indicators, while the lack of the accelerator led to a serious deficiency in early strength; in addition, the lack of any anti-dispersion component also led to a significant reduction in 28-day compressive strength (a decrease of 30% to 43%). This fully demonstrates that the four components of the aforementioned integrated low-temperature anti-dispersion additive have a significant synergistic effect on hydration strength and anti-dispersion performance in low-temperature dynamic water environment. The inventors believe the reason may be that the molecular chains of zwitterionic polyacrylamide extend and adsorb onto the negatively charged surfaces of slag and cement particles in an alkaline slurry environment, forming localized cationic microregions. These microregions electrostatically anchor the residual silanol groups on the surface of the hydrophobically modified attapulgite, causing the hydrophobically modified attapulgite to preferentially accumulate at the particle-water interface rather than randomly agglomerate. Simultaneously, the long filaments of nanocellulose associate with the amide groups of the zwitterionic polyacrylamide via hydrogen bonds, weaving their nanonetwork into the flocculent skeleton. This couples the originally separate functional layers of flocculation, hydrophobic barrier, and nano-constraint into a composite interface layer with a mechanical gradient. In this coupled interface, the hydrophobically modified attapulgite shields the wetting channels of water molecules, forcing the nanocellulose network to bear more of the hydrodynamic shear stress, while the flocculation structure of the zwitterionic polyacrylamide prevents the nanocellulose from peeling off under scouring. On the other hand, the chlorine-free low-temperature hydration accelerator rapidly anchors the aforementioned composite interface layer into a stable cementitious structure by accelerating the dissolution of calcium ions and the nucleation of hydration products at the interface, thus avoiding interface degradation caused by delayed hydration at low temperatures. This creates a cascade amplification effect, which is not significant under conventional static or ambient temperature conditions, but effectively inhibits the rearrangement of interparticle water and the propagation of microcracks under the continuous stripping action of low-temperature dynamic water on the slag particles.
Claims
1. A non-dispersible, fluidized solidified soil adapted to low-temperature dynamic water erosion, characterized in that, The raw materials for production include the following components in the following proportions by weight: 70-85 parts of pretreated construction waste, 12-25 parts of low-temperature composite cementitious system, and 1.5-3.0 parts of low-temperature anti-dispersion integrated additive; The low-temperature composite cementitious system is composed of rapid-hardening sulfoaluminate cement, slag powder, and calcium carbide slag powder in a mass ratio of 4-8:5-10:3-8. The low-temperature anti-dispersion integrated additive is composed of amphoteric polyacrylamide, hydrophobically modified attapulgite, nanocellulose, and chlorine-free low-temperature hydration accelerator in a mass ratio of 0.04-0.12:1.0-2.2:0.1-0.35:0.3-0.
5.
2. The underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring according to claim 1, characterized in that, The pretreated construction waste has a particle size ≤4.75mm and a moisture content ≤10%; the rapid-hardening sulfoaluminate cement is grade 42.5 rapid-hardening sulfoaluminate cement with a specific surface area ≥350m² / kg and an initial setting time ≤25min; the slag powder is grade S95 slag powder with a specific surface area ≥400m² / kg and a 28d activity index ≥95%; the calcium carbide slag powder is dried, ground, and passed through a 200-mesh sieve, with a Ca(OH)₂ content ≥85%.
3. The underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water erosion according to claim 1, characterized in that, The zwitterionic polyacrylamide is a copolymer of acrylamide, whose molecular chain contains both cationic and anionic groups, with a molecular weight of 8 million to 12 million, a cationicity of 10% to 30%, an anionicity of 5% to 15%, and a solid content of ≥90%.
4. The underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring according to claim 1, characterized in that, The hydrophobically modified attapulgite is prepared by surface hydrophobic modification of natural attapulgite using a silane coupling agent, with a hydrophobic contact angle ≥120° and a specific surface area ≥150m² / g.
5. The underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring according to claim 1, characterized in that, The nanocellulose is cellulose nanofiber or cellulose nanocrystal, with a diameter of 5-20 nm, a length of 200-2000 nm, and a crystallinity of ≥70%.
6. The underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring according to claim 1, characterized in that, The chlorine-free low-temperature hydration coagulant is a complex composed of triethanolamine and aluminum sulfate in a mass ratio of 1:2 to 3, or a complex composed of calcium formate and lithium carbonate in a mass ratio of 5 to 10:
1.
7. The method for preparing underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Take each raw material according to the production raw material quantity; S2. Add rapid-hardening sulfoaluminate cement, slag powder, and carbide slag powder into a dry powder mixer and stir at a low speed of 140-200 r / min for 5-10 min to ensure that the dry powder components are evenly dispersed and to obtain a premixed dry material. S3. Mix hydrophobically modified attapulgite and nanocellulose, add to mixing water, and stir in a high-speed disperser at 1000-2000 r / min for 10-15 min to fully disperse and form a stable suspension; then add zwitterionic polyacrylamide and chlorine-free low-temperature hydration accelerator, and continue stirring for 5-10 min to obtain the anti-dispersion aid pre-dispersion liquid. S4. The premixed dry material obtained in step S2 is put into a forced mixer. First, the anti-dispersion agent pre-dispersion liquid obtained in step S3 and the mixing water are added. The mixture is stirred at a low speed of 120-180 r / min for 2-4 min to form a solidifying agent slurry. Then, the pretreated construction waste is slowly added and stirred at a low speed for 5-10 min to ensure that all components are fully mixed and homogeneous, so as to obtain a fluid solidified soil slurry with a solid content of 65%-75%. S5. The fluidized solidified soil slurry prepared in step S4 is injected into the mold and cured to the specified age to obtain fluidized solidified soil.
8. The preparation method according to claim 7, characterized in that, When the construction water temperature is below 5℃, the mixing water in steps S3 and S4 is preheated to 18-22℃.
9. The preparation method according to claim 7, characterized in that, The fluidized solidified soil slurry obtained in step S4 can be used for underwater pouring within 30 minutes.
10. The application of the underwater non-dispersible fluidized solidified soil adapted to low-temperature dynamic water scouring as described in any one of claims 1 to 6 in water conservancy projects, river embankment reinforcement, underwater bridge foundation protection, or underwater pipeline covering protection.